A New Hybrid Conjugate Gradient Projection Method for Solving Nonlinear Monotone Equations - Minglei Fang; Min Wang; Defeng Ding (Journal of Mathematics)
In this study, we propose a new modified hybrid conjugate gradient projection method with a new scale parameter φk for solving large-scale nonlinear monotone equations. The proposed method includes two major features: projection techniques and sufficient descent property independent of line search technique. Global convergence of the proposed method is proved under some suitable assumptions. Finally, numerical results illustrating the robustness of the suggested strategy and its comparisons are shown.